Evaluation of women entrepreneurship performance in OECD countries - Data Envelopment Analysis approach - Ateş, Melda Güliz; Özcan Türkkan, Burcu; Şahin, Yıldız (Afyon Kocatepe Üniversitesi)
The importance of women entrepreneurship increases day by day as it has a significant contribution to economic development, job creation, and innovation. Thus, policymakers put more emphasis on the criticality of standardized data, comparative studies, and measurement methods for women's entrepreneurship because these are essential to developing public policy and incentive/support systems. Within the scope of the study, women entrepreneurship performance of OECD countries was evaluated via Data Envelopment Analysis (DEA) and a comparative analysis presented. Input-oriented Charnes Cooper Rhodes (CCR) model was used and the established model was solved using EMS (Efficiency Measurement System). Results show that 11 countries (Denmark, Finland, France, Greece, Lithuania, Luxembourg, Netherlands, Norway, Portugal, Sweden, Switzerland) are efficient countries with their women entrepreneurship performance and as an output of the analysis the inefficient countries and their references are shared. Turkey took 29th place among 30 countries in the means of women entrepreneurship performance and Turkey, France, and Portugal should be taken as references for the improvement activities.

Kadın girişimciliğinin önemi ekonomik kalkınmaya, istihdam yaratılmasına ve yenilikçiliğe katkısından dolayı her geçen gün artmaktadır. Bu nedenle, politika yapıcılar, standartlaştırılmış verilerin, karşılaştırmalı çalışmaların ve kadın girişimciliği için ölçüm yöntemlerinin kritikliğine daha fazla vurgu yapmaktadır; zira, bunlar, kamu politikası ve teşvik / destek sistemleri geliştirmek için gereklidir. Çalışma kapsamında OECD ülkelerinin kadın girişimcilik performansı Veri Zarflama Analizi (VZA) ile değerlendirilmiş ve karşılaştırmalı bir analiz sunulmuştur. Girdi yönelimli Charnes Cooper Rhodes (CCR) modeli kullanılmış ve oluşturulan model EMS (Efficiency Measurement System) kullanılarak çözülmüştür. Sonuçlar, 11 ülkenin (Danimarka, Finlandiya, Fransa, Yunanistan, Litvanya, Lüksemburg, Hollanda, Norveç, Portekiz, İsveç, İsviçre) kadın girişimcilik performansları ile verimli ülkeler olduğunu göstermiş ve analizin çıktısı olarak verimsiz ülkeler ile referansları paylaşılmıştır. Türkiye, kadın girişimcilik performansı açısından 30 ülke arasında 29. sırada yer alırken, iyileştirme faaliyetleri için Fransa ve Portekiz’i referans alma gerekliliği tespit edilmiştir.
OECD ülkelerinin kadın girişimciliği performanslarının değerlendirilmesi – Veri Zarflama Analizi uygulaması
Keywords: Woman Entrepreneurship; Measurement of Woman Entrepreneurship; Data Envelopment Analysis; DEA